Ultra-small palladium nano-particles synthesized using bulky S/Se and N donor ligands as a stabilizer: application as catalysts for Suzuki–Miyaura coupling. Issue 39 (18th July 2019) - Oswal, Preeti; Arora, Aayushi; Kaushal, Jolly; Rao, Gyandshwar Kumar; Kumar, Sushil; Singh, Ajai K.; Kumar, Arun
Abstract : Monodispersed ultrasmall Pd nanoparticles synthesized utilizing bulky organochalcogen secondary amines as stabilizers and application in Suzuki coupling of aryl chlorides at low catalyst loading. Abstract : Two chalcogenated ligandsL1 andL2 containing anthracene core and amine functionality have been synthesized. Both the ligands have been characterized using 1 H and 13 C 1 H NMR techniques. The structure ofL1 has also been corroborated by single crystal X-ray diffraction. Application ofL1 andL2 as stabilizers for palladium nano-particles (NPs) has been explored and six different types of NPs1–6 have been prepared by varying the quantity of stabilizer. The nano-particles have been characterized by PXRD, EDX, and HRTEM techniques. The size of NPs has been found to be in the range of ∼1–2 nm, 2–3 nm, 4–6 nm, 1–2 nm, 1–2 nm and 3–5 nm for1–6 respectively. The catalytic activities of1–6 have been explored for Suzuki–Miyaura coupling of phenyl boronic acid with various aryl halides. These NPs showed good catalytic activity for various aryl chlorides/bromides at low catalyst loading (5 mg). Among1–6, the highest activity has been observed for NPs1, probably due to their relatively small size and high uniformity in the dispersion. The recyclability of the NPs upto 5 catalytic cycles is a distinct advantage.